Fluence inhomogeneities due to a ripple filter induced Moiré effect - Ringbæk, Toke Printz; Brons, Stephan; Naumann, Jakob; Ackermann, Benjamin; Horn, Julian; Latzel, Harald; Scheloske, Stefan; Galonska, Michael (Physics in medicine and biology, 2015)
At particle therapy facilities with pencil beam scanning, the implementation of a ripple filter (RiFi) broadens the Bragg peak, so fewer energy steps from the accelerator are required for a homogeneous dose coverage of the planning target volume (PTV). However, sharply focusing the scanned pencil beams at the RiFi plane by ion optical settings can lead to a Moiré effect, causing fluence inhomogeneities at the isocenter. This has been experimentally proven at the Heidelberg Ionenstrahl-Therapiezentrum (HIT), Universitätsklinikum Heidelberg, Germany. 150 MeV u −1 carbon-12 ions are used for irradiation with a 3 mm thick RiFi. The beam is focused in front of and as close to the RiFi plane as possible. The pencil beam width is estimated to be 0.78 mm at a 93 mm distance from the RiFi. Radiographic films are used to obtain the fluence profile 30 mm in front of the isocenter, 930 mm from the RiFi. The Monte Carlo (MC) code SHIELD-HIT12A is used to determine the RiFi-induced inhomogeneities in the fluence distribution at the isocenter for a similar setup, pencil beam widths at the RiFi plane ranging from ##IMG## [http://ej.iop.org/images/0031-9155/60/3/N59/pmb506424ieqn001.gif] $σ _x^\textRiFi=0.56$ to 1.2 mm and for scanning step sizes ranging from 1.5 to 3.7 mm. The beam application and monitoring system (BAMS) used at HIT is modelled and simulated. When the width of the pencil beams at the RiFi plane is much smaller than the scanning step size, the resulting inhomogeneous fluence distribution at the RiFi plane interfers with the inhomogeneous RiFi mass distribution and fluence inhomogeneity can be observed at the isocenter as large as an 8% deviation from the mean fluence. The inverse of the fluence ripple period at the isocenter is found to be the difference between the inverse of the RiFi period and the inverse of the scanning step size. We have been able to use MC simulations to reproduce the spacing of the ripple stripes seen in films irradiated at HIT. Our findings clearly indicate that pencil beams sharply focused near the RiFi plane result in fluence inhomogeneity at the isocenter. In the normal clinical application, such a setting should generally be avoided.